The United States and Iraq since 1990 a brief history with documents - McNamara, Robert S., 1916-2009; Brigham, Robert K. (Wiley-Blackwell, 2014)
"This book offers a concise history of US policy in Iraq since 1990 and how it has evolved over two decades. -Examines US relations with Iraq from both a regional and international perspective -Argues that the only way to clearly understand US policy toward Iraq is to see it in its proper historical context and within a transnational framework -Uses recently declassified documents at the end of each chapter to illustrate US decision-making in the wars for Iraq -Addresses the importance of the changing domestic climate surrounding two decades"--